Design, characterization, and evaluation of eco-friendly etofenprox-loaded ethosomes to control Ceratitis capitata (Diptera: Tephritidae) - Francesco Corrias; Ines Castangia; Salvatore Marceddu; Roberto Mannu; Arturo Cocco; Maria Letizia Manca; Gabriele Ibba; Maria Manconi; Ignazio Floris; Alberto Angioni (Scientific Reports)
Abstract Ceratitis capitata, is one of the most considerable invasive pests affecting fruit production worldwide. Conventional pesticides are generally formulated using organic solvents and emulsifiers that, in turn, are flammable and toxic. Thanks to their small size and biocompatibility, liposome-like formulations may significantly improve the efficacy and safety of conventional pesticides. This study aims to develop an alternative and innovative etofenprox formulation based on phospholipid vesicles (ethosomes) and evaluate its possible application for agricultural pest control. Ethosomes and geraniol-ethosomes were prepared by the one-step sonication method, achieving vesicles with small sizes (around 267 nm) and low polydispersity index (around 0.04). These vesicles were stable over 90 days of storage at room temperature and could slow the release of etofenprox (57 ± 4% released), in comparison with a commercial formulation (85 ± 5% released) after 24 h. Ethosomes and geraniol-ethosomes showed similar retention properties on lemon leaves (13.3 ± 1.0 to 14.4 ± 1.2 mg/cm2) under laboratory condition. After open-field application, geraniol-ethosomes left the highest etofenprox residues on lemon leaves (14.3 ± 1.0 mg/kg), whereas the commercial formulation on the flavedo (4.1 ± 0.5 mg/kg). This result highlighted the possibility of reducing the application dose of etofenprox loaded in geraniol-ethosomes especially during the BBCH stage before fruiting. Both formulations displayed good biocompatibility with no significant cytotoxic effects on human keratinocytes (HaCat cells) across different etofenprox concentrations. Furthermore, laboratory bioassays revealed that geraniol-ethosomes exhibited a prolonged toxicity when sprayed against Ceratitis capitata adults, attributed to sustained release kinetics, underscoring their potential in environmentally sustainable agricultural pest management.